More money, milk and meat: Promoting mass artificial insemination for Ethiopian cattle - International Livestock Research Institute (International Livestock Research Institute, 2014)
Produced about the work of the Improving Productivity and Market Success (IPMS) of Ethiopian Farmers project. The film was originally done in October 2013. It explains how 'mass artificial insemination' of cattle combined with hormone synchronization and sex fixing benefits Ethiopia's cattle owners.